Very Short Peptides with Stable Folds: Building on the Inter-relationship of Trp/Trp, Trp/cation, and Trp/backbone-amide Interaction Geometries - Eidenschink, Lisa (2009)
By combining a favorable turn sequence with a turn flanking Trp/Trp interaction and a C-terminal H-bonding interaction between a backbone amide and an i - 2 Trp ring, a particularly stable (ΔG(U) > 7 kJ/mol) truncated hairpin, Ac-WI-(D-Pro-D-Asn)-KWTG-NH(2), results. In this construct and others with a W-(4-residue turn)-W motif in severely truncated hairpins, the C-terminal Trp is the edge residue in a well-defined face-to-edge (FtE) aryl/aryl interaction. Longer hairpins and those with six-residue turns retain the reversed “edge-to-face” Trp/Trp geometry first observed for the trpzip peptides. Mutational studies suggest that the W-(4-residue turn)-W interaction provides at least 3 kJ/mol of stabilization in excess of that due to the greater β-propensity of Trp. The β-propensity of Trp is context dependent; but, for the systems studied, always greater than that of Thr (by 0.4 - 4.7 kJ/mol). At non-H-bonded positions remote from the turn, two alternative edge-to-face geometries are observed and there is no evidence of additional stabilization due to the Trp/Trp interaction. The NMR structuring shift diagnostics of edge-to-face Trp/Trp, Trp/Lys π-cation, and Trp/Gly-H(N) interactions have been defined. The latter can give rise to > 3 ppm upfield shifts for the Gly-H(N) in -WX(n)G- units both in turns (n = 2) and at the C-termini (n = 1) of hairpins. Terminal YTG units result in somewhat smaller shifts (extrapolated to 2 ppm for 100% folding). In peptides with both the EtF and FtE W/W interaction geometries, Trp to Tyr mutations indicate that Trp is the preferred “face” residue in aryl/aryl pairings, presumably due to its greater π basicity.